Galactgogue effects on Musa x paradisiaca flower extract on the lactating rats - Mahmood, Azizah; Omar, Muhammad Nor; Ngah, Nurziana (Elsevier, 2012)
Objective To investigate the potential of Musaxparadisiaca (M. xparadisiaca) flower extracts in promoting milk production of lactating rats and its effects on growth of the suckling pups.